Asymmetric total synthesis of (-)-renieramycin G and studies toward the total synthesis of ecteinascidin-743 - Jin, Wei, author; William, Robert, advisor (Colorado State University. Libraries, 2004)
An efficient and asymmetric synthesis of a highly functionalized tetrahydroisoquinoline is presented, of which the key reactions are a sequential asymmetric Staudinger ketene-imine β-lactam-forming reaction and a Pictet-Spengler cyclization. An efficient method to make a versatile chiral amino acid for tetrahydroisoquinoline antitumor alkaloids is also reported. The synthesis features an alkylation reaction with a chiral glycinate template that sets the stereocenter of the amino acid. Additionally, the coupling of the tetrahydroisoquinoline and the amino acid leads to the asymmetric synthesis of a versatile pentacycle, which could potentially be used in the total synthesis of members of the ecteinascidin/saffamycin/safracin/renieramycin family of antitumor alkaloids. Finally, the approach to construct the pentacycle is applied to the first asymmetric total synthesis of (-)-renieramycin G.
Keywords: organic chemistry; oncology